Design and Implementation of Efficiency Improved DC-DC Boost Converter - Scaria, Jeneesh; Sebastian, Preethy; Nanan, Susan V (International Journal of Computer Sciences and Engineering, 2025)
This paper proposes the design and simulation of a DC-DC Boost converter employing PID controller, enhancing overall performance of the system. The main objective of a DC- DC converter is to maintain a constant output voltage despite variations in input/source voltage, components and load current. Designers aim to achieve better conversion efficiency, minimized harmonic distortion and improved power factor while keeping size and cost of converter within acceptable range. A simple PID (Proportional, Integral and Derivative) controller has been applied to a conventional Boost converter and tested in MATLAB-Simulink environment achieving improved voltage regulation. The proposed closed loop implementation of the converter maintains constant output voltage despite changes in input voltage and significantly reduces overshoot thereby improving the efficiency of the converter. The output of this investigation has the potential to contribute in a significant way in electric vehicles, industry, communication and renewable energy sectors.